2002
DOI: 10.1152/ajpgi.00503.2001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for a glycine-gated chloride channel in macrophages and leukocytes

Abstract: Recent studies have demonstrated that glycine blunts the response of Kupffer cells to endotoxin. Based on pharmacological evidence, it was hypothesized that Kupffer cells and other macrophages contain a glycine-gated chloride channel similar to the glycine receptor expressed in neuronal tissues. Moreover, glycine stimulates influx of radiolabeled chloride in Kupffer cells in a dose-dependent manner. RT-PCR was used to identify mRNA of both alpha- and beta-subunits of the glycine receptor in rat Kupffer cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
99
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 34 publications
11
99
0
2
Order By: Relevance
“…However, 0.5, 1, and 2 mmol/L GLY significantly attenuated 100 µg/mL LPS-induced TNFα release from the cardiomyocytes ( Figure 1B). [17] , and GLY stimulates the GLY-gated chloride channel, resulting in chloride influx and hyperpolarization of the membrane, which in turn blunts the increase in [Ca 2+ ] c in leukocytes [5] . Thus, it is necessary to examine the effect of GLY on Ca 2+ influx in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, 0.5, 1, and 2 mmol/L GLY significantly attenuated 100 µg/mL LPS-induced TNFα release from the cardiomyocytes ( Figure 1B). [17] , and GLY stimulates the GLY-gated chloride channel, resulting in chloride influx and hyperpolarization of the membrane, which in turn blunts the increase in [Ca 2+ ] c in leukocytes [5] . Thus, it is necessary to examine the effect of GLY on Ca 2+ influx in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that LPS at concentrations less than 10 µg/mL induces an increase in [Ca 2+ ] c mainly via intracellular calcium release. A previous study suggested that GLY inhibited calcium influx mainly from the extracellular space [5] . Therefore, the inhibitory amplitude of 2 mmol/L GLY on [Ca 2+ ] c elevation in cardiomyocytes exposed to 1 and 10 µg/mL LPS is not enough to inhibit TNFα production.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations